The effects of a video-aided imagery intervention upon collective efficacy in an international paralympic wheelchair basketball team - Shearer, D.; Mellalieu, S.; Shearer, C.; Roderique-Davies, G. (Journal of Imagery Research in Sport and Physical Activity, 2009)
A multiple baseline across groups design was used to examine the effects of an imagery intervention on perceptions of collective efficacy. Members (n = 10) from an international wheelchair basketball team were separated into three regional intervention groups. Each group completed a 4 week, video-aided, motivational general-mastery (MG-M) type imagery program with team content. Collective efficacy was measured via the Collective Efficacy Inventory (Callow, Hardy, Markland, & Shearer, 2004). Collective efficacy increased for the South group and became more consistent for the Midlands group. No changes were reported for the North group. Social validation measures indicated potential mechanisms via imagery effects on individual perceptions of self-efficacy and then collective efficacy. The results provide partial support for the use of MG-M type imagery interventions to enhance both individual and team perceptions of collective efficacy in elite wheelchair basketball.